Sensitivity analysis of friction force model parameters in multibody dynamics - Marques, Pedro Filipe Lima (2016)
A sensitivity analysis of the parameters of the most relevant friction force models for multibody dynamics is provided in this work. For this, Dahl, Reset Integrator, LuGre and Gonthier models are revisited. The classic single degree-of-freedom mass-spring model is utilized to analyze the influence parameters. The results are presented through the friction-displacement and friction-velocity relations. Although some of the parameters show different impact according to the model used, most of them presents the same tendency. This investigation allows for the identification of the parameters that can more affect the systems’ response in terms of accuracy.